PERSEPSI GURU PAMONG TERHADAP KETERAMPILAN MENGAJAR MAHASISWA PPL TAHUN AJARAN 2017/2018 - Ramdani, Rahmat; Khosmas, F.Y.; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is the perception of teacher pamong to the skills of teaching the students PPL 2 economic education in SMAN 7 Pontianak, SMAN 9 Pontianak and SMA Islamiyah Pontianak academic year 2016/2017. Three PPL students and three teachers of Pamong became the source of data in three different schools. The form of research that researchers use is the form of survey studies that conduct assessment, depiction and disclosure about the perception of teachers pamong to the skills of teaching PPL students. Data collection techniques used in this research are (1) direct communication techniques with interview guidance tools; (2) indirect communication techniques with observation guidance tools; (3) documentary study techniques in the form of documents. From the results of research on the perception of teachers pamong on the skills of teaching students PPL in SMAN 7 Pontianak, SMAN 9 Pontianak and SMA Islamiyah Pontianak was quite good in skills to provide strengthening, skills to make variations, skills open and close lessons, classroom management skills, and group teaching skills small & individual. But there are some teaching skills that have not been mastered by PPL students such as questioning skills, explaining skills, and skills to guide small group discussions. Keywords: Perception of Teachers, Teaching Skills Student PPl